Cardiovascular response to hypoxia after endurance training at altitude and sea level and after detraining - Katayama, K.; Sato, Y.; Morotome, Y.; Shima, N.; Ishida, K.; Mori, S.; Miyamura, M. (Journal of Applied Physiology, 2000)
even with the following address: http://jap.physiology.org/cgi/content/abstract/88/4/1221